2021
DOI: 10.1128/jcm.00158-21
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance of Latest-Generation and FDA-Cleared Serology Tests for the Diagnosis of Chagas Disease

Abstract: Confirmed diagnosis of chronic Chagas disease (CD) requires positive results by two different IgG serology tests. Variable sensitivity has been reported among tests and in different endemic regions. Inadequate specificity presents a particular challenge in low prevalence settings such as the United States. This study provides a direct comparison of the latest-generation IgG serology assays with four previously assessed FDA-cleared tests. Seven hundred and ten blood donor plasma specimens were evaluated by Wien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 28 publications
1
17
0
1
Order By: Relevance
“…In Mexico, very few women had high antibody levels, and most of them had no antibodies against test antigens. Such differences in antibody levels against test antigens are similar to those reported in U.S. blood donors coming from different countries in Latin America ( 12 ) and could be due to differences in immune response (host genetic diversity) and/or difference in antigens (parasite diversity). Interestingly, the recently described reference serum standards derived from samples from Mexico, thought to be infected with TcI, and samples from Brazil and Argentina, thought to be infected with TcII, seem to present some differences in OD reading between the two pools of samples ( 25 ), suggesting different antibody levels against ELISA antigens among these countries.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In Mexico, very few women had high antibody levels, and most of them had no antibodies against test antigens. Such differences in antibody levels against test antigens are similar to those reported in U.S. blood donors coming from different countries in Latin America ( 12 ) and could be due to differences in immune response (host genetic diversity) and/or difference in antigens (parasite diversity). Interestingly, the recently described reference serum standards derived from samples from Mexico, thought to be infected with TcI, and samples from Brazil and Argentina, thought to be infected with TcII, seem to present some differences in OD reading between the two pools of samples ( 25 ), suggesting different antibody levels against ELISA antigens among these countries.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, variations in test performance among regions and countries have been reported before ( 8 ), particularly in Mexico ( 9 , 10 ). A recent assessment of test performance among U.S. blood donors indicated that for all tests evaluated, antibody reactivity and clinical sensitivity were lowest in donors from Mexico, intermediate in those from Central America, and highest in those from South America, although minimum sensitivity reached at least 82.6% ( 11 , 12 ). In a previous study, we screened pregnant women for T. cruzi infection in a large multicentric study in Argentina, Honduras, and Mexico to assess congenital transmission ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is no gold standard for the diagnosis of CD, requiring at least two distinct serological assays. Different ELISA assays for detecting Chagas are commercially available, although variations in their performance when testing samples from different countries have been reported [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Despite sustaining "hundreds" of bites from triatomines over a 10-year period, frequently finding them inside his home, and evidence of T. cruzi-infected triatomines collected from inside the home, our patient did not have clinical or serological evidence of chronic CD. There has been some concern that certain T. cruzi DTU strains found within certain geographic regions in Mexico, as well as Central and South America, have discordant serological testing results [29][30][31][32]. The sensitivity and specificity of our available CD serological tests have not been assessed among those with autochthonous CD in the US at this time.…”
Section: Discussionmentioning
confidence: 99%